2021
DOI: 10.1039/d0ra09703a
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of Wuyi rock tea with different roasting degrees and their discrimination based on volatile profiles

Abstract: Wuyi rock tea is a typical and famous oolong tea in China and roasting is an important manufacturing procedure for its flavor formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Naphthalene, 1-methylnaphthalene and 2-methylnaphthalene contributed with pungent and herbal-like notes, which could be degraded by microorganisms ( Tanguler, Selli, Sen, Cabaroglu, & Erten, 2017 ). Naphthalene with pungent note, converted from long-chain hydrocarbons, was identified as the key odorant in yellow tea and Wuyi rock tea ( Liu et al, 2021 , Shi et al, 2021 ). 1-Methylnaphthalene also possessing pungent note was reported to contribute to the aroma of Liupao tea, which was usually used as a potential indicator to evaluate the degree of fermentation ( Ma et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Naphthalene, 1-methylnaphthalene and 2-methylnaphthalene contributed with pungent and herbal-like notes, which could be degraded by microorganisms ( Tanguler, Selli, Sen, Cabaroglu, & Erten, 2017 ). Naphthalene with pungent note, converted from long-chain hydrocarbons, was identified as the key odorant in yellow tea and Wuyi rock tea ( Liu et al, 2021 , Shi et al, 2021 ). 1-Methylnaphthalene also possessing pungent note was reported to contribute to the aroma of Liupao tea, which was usually used as a potential indicator to evaluate the degree of fermentation ( Ma et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The first comprehensive study found >80 volatile compounds in Dangui WRT by application of solid-phase microextraction (SPME) sampling technique and GC–MS; therein, farnesene, geraniol, hexyl hexanoate, indole, and trans -nerolidol were reported as the main aroma constituents . To date, studies on a variety of WRT volatiles such as Rougui , Qizhong , and Dahongpao have reported >400 volatile components in WRT. Because only a small part of volatiles can be recognized by human’s olfactory perception and leads to the specific aroma profile of a foodstuff, an activity-guided methodology called the sensomics approach is applied in flavor research studies as the state-of-the-art approach to elucidate the role of individual aroma-active compounds . Recently, several research studies applied gas chromatography–olfactometry (GC–O) and orthonasal odor thresholds (OTs) to estimate the influence of odorants on the aroma qualities of different WRT varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Wuyi rock tea (WRT), a unique subclass of oolong tea, is produced in northern Fujian, China, where the most suitable soil and climate are provided . It is famous for the abundant flavor and long-lasting taste that is called “rock charm and floral fragrance” or “ Yan flavor” in China. , Rougui is one of the classical cultivars to process WRT, as the saying goes, “The premium aroma of Rougui could not be surpassed by any other cultivars in WRT”. Besides, Shuixian and Dahongpao are also popular and major cultivars to produce WRT …”
Section: Introductionmentioning
confidence: 99%